Experiences with thermal ablation for cervical precancer treatment after self‐collection HPV‐based screening in the ASPIRE Mayuge randomized trial. Issue 8 (28th November 2022) - Gottschlich, Anna; Payne, Beth A.; Trawin, Jessica; Albert, Arianne; Jeronimo, Jose; Mitchell‐Foster, Sheona; Mithani, Nadia; Namugosa, Ruth; Naguti, Priscilla; Orem, Jackson; Rawat, Angeli; Simelela, Princess Nothemba; et al.
Abstract: Cervical cancer remains a significant public health burden in low‐resourced countries. Thus, the WHO prioritized cervix screening, and recently recommended thermal ablation treatment for cervical precancer. However, there is limited information on side effects during treatment and recovery, and acceptability among those treated. The ASPIRE Mayuge trial recruited women to participate in self‐collection cervix screening between 2019 and 2020 (N = 2019). Screen‐positive women (N = 531, 26.3%) were referred for visual inspection with acetic acid and thermal ablation treatment, per Uganda Ministry of Health recommendations; 71.2% of those referred attended follow‐up. Six months post‐screening, a subset of trial participants were recontacted. Those who received thermal ablation completed a survey assessing side effects during and after the procedure, and willingness to recommend the treatment to others. We summarized the results to describe the side effects and acceptability of thermal ablation treatment. Of 2019 participants, 349 (17%) received thermal ablation. A subset of 135 completed the follow‐up survey, where 90% reported pain during treatment; however, intensity and duration were low. Over a third of women reported problems with recovery for reasons including pain, discharge and bleeding. Regardless, 98% reported they would recommend the treatment to others. The use of thermal ablation to treat cervical precancer appears to be highly acceptable in this population. While many women reported side effects during the procedure and recovery, the majority said they would recommend the treatment to others. However, given the substantial proportion who reported problems with recovery, efforts should be made to provide additional resources to women after receiving thermal ablation treatment for cervical precancer. Abstract : What's new? While thermal ablation is effective in treating cervical precancer in low‐resourced settings, whether its side effects are acceptable to patients remains unclear. The present study investigated the experiences of women who received thermal ablation after testing positive for human papillomavirus infection as part of a cervical cancer screening trial in Uganda. About 90% of women who completed surveys reported mild pain while undergoing thermal ablation. One‐third of patients reported issues with discharge, pain and bleeding during recovery. Nonetheless, nearly all women treated with thermal ablation reported the procedure as highly acceptable, with high likelihood of recommendation to others.